Convergence in public health expenditure across the Sub-Saharan African countries: Does club convergence matter? - Ousmane Traoré (Health Economics Review, 2021)
Background: Sub-Saharan African (SSA) countries that currently face enormous healthcare challenges have implemented national health policies focusing on regional or international health commitments. These health commitments generally promote new healthcare financing policies (e.g., health insurance, user fee exemption and results-based financing) with the objective of providing ever-larger population cohorts with human capital and better health in particular. To achieve this, governments must involve themselves more fully in their respective healthcare sectors through the mobilisation of public funding. Objective: This paper aims to examine convergence in health expenditure throughout SSA. The findings of club convergence will allow a robust comparison of health indicators between countries and will be suitable for the adjustment of health policies to foster the efficiency of such policies at the regional and/or country level. Such findings could also help with the conception and implementation of health policies at the regional level. Methods: We used the methodology of convergence analysis based on dynamic factor modelling leading to the logt regression to test for full convergence, club convergence and club clustering of health expenditure on a balanced panel of 44 countries in Sub-Saharan Africa spanning the period from 2000 to 2016. Results: Overall, our results do not support the hypothesis that all SSA countries converge to a single equilibrium state regarding public health expenditure. When testing for club convergence, the results highlight eight convergence clubs and one group of diverging countries. Indeed, performing the club clustering algorithm reveals the existence of three convergence clubs and the diverging group. The three clubs consist of 12, 14 and 14 members, respectively, where convergence is found to occur among different regional economic organisations. Conclusion: Our findings indicate that SSA governments should increase spending on healthcare in order to align their healthcare systems with a global convergence model. To foster the convergence to a single equilibrium state in public health expenditure, attention could be paid to strengthening integration within the various regional economic organisations and to the coordination and integration of healthcare policies within and across convergence clubs throughout SSA.
Keywords: 330; Health expenditure; Club convergence; log t regression; Sub-Saharan Africa